Research update: Strategies for improving the stability of perovskite solar cells - Habisreutinger, S; McMeekin, D; Snaith, H; Nicholas, R (AIP Publishing, 2016)
The power-conversion efficiency of perovskite solar cells has soared up to 22.1% earlier this year. Within merely five years, the perovskite solar cell can now compete on efficiency with inorganic thin-film technologies, making it the most promising of the new, emerging photovoltaic solar cell technologies. The next grand challenge is now the aspect of stability. The hydrophilicity and volatility of the organic methylammonium makes the work-horse material methylammonium lead iodide vulnerable to degradation through humidity and heat. Additionally, ultraviolet radiation and oxygen constitute stressors which can deteriorate the device performance. There are two fundamental strategies to increasing the device stability: developing protective layers around the vulnerable perovskite absorber and developing a more resilient perovskite absorber. The most important reports in literature are summarized and analyzed here, letting us conclude that any long-term stability, on par with that of inorganic thin-film technologies, is only possible with a more resilient perovskite incorporated in a highly protective device design.